Mostly harmless - Adams, Douglas, 1952-2001. (New York : Ballantine Books, 2000)
Vascillating between two realities--one in which Earth exists and one in which it has been destroyed by the Vogons--bizarre adventures arise for Ford Prefect and Arthur Dent, including Ford's discovery that the "Hitchhiker's Guide to the Galaxy" headquarters have been overtaken, and Arthur's discovery that he has a teenage daughter.
Library Journal.
Wilson's Fiction.
Wilson's Senior High School.
Book Report, April 2006.
Library Journal, March 2006.
New York Times, August 2006.
Keywords: Dent, Arthur (Fictitious character) -- Fiction; Interplanetary voyages -- Fiction; Prefect, Ford (Fictitious character) -- Fiction; Dent, Arthur (Fictional character) -- Fiction; Interplanetary voyages -- Fiction; Prefect, Ford (Fictional character) -- Fiction; Science fiction